2018
DOI: 10.1108/ijchm-12-2016-0659
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological contract fulfillment on organizational citizenship behavior

Abstract: Purpose This study aims to investigate the impact of psychological contract fulfillment (PCF; independent) on organizational citizenship behavior (OCB; dependent) with perceived organizational support (POS) playing a partial mediating role. Design/methodology/approach Quantitative methodology has been adopted to achieve the aim of this study, and data were collected via a questionnaire through an employee–supervisor/colleague dyad. Various five- and four-star hotel staff members in Pakistan were the target p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
118
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 42 publications
14
118
0
3
Order By: Relevance
“…To date, extant research has identified many determinants of OCB such as perception of organizational politics (Khan et al, 2019), emotional intelligence (Lim et al, 2018), perceived organizational support (Dai et al, 2018), psychological contract fulfillment (Ahmad and Zafar, 2018), and ethical leadership (Yang and Wei, 2017;Mostafa, 2018). However, little is known about whether humble leadership can affect OCB, and the potential mechanisms accounting for this relationship is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…To date, extant research has identified many determinants of OCB such as perception of organizational politics (Khan et al, 2019), emotional intelligence (Lim et al, 2018), perceived organizational support (Dai et al, 2018), psychological contract fulfillment (Ahmad and Zafar, 2018), and ethical leadership (Yang and Wei, 2017;Mostafa, 2018). However, little is known about whether humble leadership can affect OCB, and the potential mechanisms accounting for this relationship is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…When a psychological contract is fulfilled, employees become committed to their organisation (Akinbobola & Zamani, 2018). As a result, employees reciprocate by engaging in organisational citizenship behaviour: beneficial activities that go beyond their formal job duties in order to benefit their employers (Ahmad & Zafar, 2018). This assertion is described by the Social Exchange Theory, one of the most powerful conceptual paradigms for understanding workplace behaviour (Cropanzano, Anthony, Daniels & Hall, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the psychological contract is considered an essential or nonnegligible element for the modern business (Coyle-Shapiro and Kessler, 2000;Aselage and Eisenberger, 2003). Nevertheless, the idea that enterprise size, psychological contract practices and individual behavior are positively related is not yet universally endorsed, and the antecedents, as well as an operational mechanism for psychological contract, also attracted extensive attentions among researchers of different national backgrounds (Robinson and Morrison, 2000;Hui et al, 2004;Ahmad and Zafar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Turnley et al (2003) examined the relationship between PCF and three types of employee behavior and found that psychological contract fulfillment is more strongly related to citizenship behavior directed at the organization than to citizenship behavior directed at one's colleagues. According to Ahmad and Zafar (2018), PCF has a positive impact on perceived organizational support (POS) and organizational citizenship behavior (OCB). The partial mediating role of POS between the dependent and independent variables was also confirmed.…”
Section: Introductionmentioning
confidence: 99%